Delay discounting and the use of mindful attention versus distraction in the treatment of drug addiction: A conceptual review. Issue 1 (25th December 2014) - Ashe, Melinda L.; Newman, Michelle G.; Wilson, Stephen J.
<x xml:space="preserve">Abstract</x> In recent decades, researchers have integrated measurements of delay discounting, how the subjective valuation of a reward changes as a function of time, into their study of addiction. Research has begun to explore the idea that delay discounting may serve as both a marker for the effectiveness of existing treatments for addiction and a potential target for novel intervention strategies. As this work is in its infancy, many potentially significant connections between the construct of delay discounting and the treatment of addiction have yet to be explored. Here, we present a conceptual review highlighting novel points of intersection between delay discounting and two approaches to treating addiction that have become increasingly popular in recent years: those that focus on the development of mindfulness skills and those that emphasize the use of distraction techniques. Viewing these two techniques through the lens of delay discounting is particularly intriguing because of the very different way that they address the experience of drug cravings in the present moment (nonjudgmentally attending to vs. shifting attention away from subjective cravings, respectively). We propose that these opposing strategies for dealing with cravings may interact with delay discounting in ways that have important implications for treatment effectiveness.